Die sonntägliche Eucharistiefeier – Fest des Lebens : Romano Guardinis Worte zum Sonntag mit einer liturgietheologischen Weiterführung - Amrehn, Timo (Ex fonte, 2025)
Ongoing and often controversial debates increasingly raise the question whether the continued observance of traditional (Eucharistic) Sunday morning services remains appropriate in the contemporary context. In view of far-reaching transformations in society, numerous voices are calling for a critical (self-)reflection: Can Sunday still be preserved? Would something be lost if the celebration of the death and resurrection of Jesus Christ were to cease – or could Sunday, particularly in its Eucharistic form, be consigned to the liturgical archive without significant loss? To address the meaning and theological significance of Sunday, selected writings by Romano Guardini will first be examined. Building on this foundation, further liturgical-theological perspectives are discussed, especially in view of vulnerability as a key concept for a theologically grounded interpretation of the present.